2013
DOI: 10.4236/ojra.2013.34041
|View full text |Cite
|
Sign up to set email alerts
|

3D Morphological Study of the Indian Arthritic Knee: Comparison with Other Ethnic Groups and Conformity of Current TKA Implant*

Abstract: Background: Studies have shown that there are striking variations in knee morphology between Asian and Western population. However, most of the existing total knee arthroplasty (TKA) implants are designed to suit the anatomy of Western population. Our study investigated anthropometry of Indian arthritic knees and compared them to international ethnic groups. Methods: Computed tomography was used to create 3D knee models and obtain anthropometric data of distal femur and proximal tibia of Indian arthritic knees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 15 publications
2
32
2
3
Order By: Relevance
“…According to various research studies, Asian knees are generally smaller than the Western population [3]- [5] [8] [12]. Moreover, a study has also demonstrated that Asian knees have a smaller aspect ratio than those of the Western population [8]. Since components of the knee implants are required to cover maximum resected surface in order to achieve a successful outcome [2] [3], it is important to know the exact morphology of the resected surface of the Indian knees in order to design or validate knee prostheses for the Indian population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to various research studies, Asian knees are generally smaller than the Western population [3]- [5] [8] [12]. Moreover, a study has also demonstrated that Asian knees have a smaller aspect ratio than those of the Western population [8]. Since components of the knee implants are required to cover maximum resected surface in order to achieve a successful outcome [2] [3], it is important to know the exact morphology of the resected surface of the Indian knees in order to design or validate knee prostheses for the Indian population.…”
Section: Discussionmentioning
confidence: 99%
“…At present, owing to a shortage of data on the distal femur and proximal tibia in this population, implants designed for knees of the Western population are being used without modifications for the ethnic group [7]. Anthropometric studies have shown that there are striking variations in knee morphology between the Asian and Western population [8]. Research on implant mismatching carried out in various Asian countries has led to the conclusion that the Asian-Pacific population should have special designs of TKA implants [9].…”
Section: Introductionmentioning
confidence: 99%
“…Maximal implant coverage on the bone surface minimizes the stress applied to the bone-implant interface [4,5] . Most TKA prosthesis designs are based on the anthropometry of western population, which differs from Asian knee morphometry [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Being shortage of data on the morphometry of distal femur and proximal tibia in the Indian population, implants designed for knees of the western population are being used without modifications for the ethnic group [2] . Anthropometric studies have shown that there are striking variations in knee morphology between the Asian and western population [3] . In TKA, maximal implant coverage on the bone surface minimizes the stress applied to the bone-implant interface [4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…2,3,6,7 A thorough understanding of the anatomic relationships of these parameters is of much clinical value. 4,9 Significant morphological variations are noted in literature between ethnic groups 16 , 17 . The studies in Asian population primarly focus on East Asian population with little literature referencing the South Asian community who are ethinically different.…”
Section: Introductionmentioning
confidence: 99%